Characterization of Alzheimer's disease‐like neuropathology in Duchenne's muscular dystrophy using the DBA/2J mdx mouse model. Issue 1 (11th November 2021) - Hayward, Grant C.; Caceres, Daniela; Copeland, Emily N.; Baranowski, Bradley J.; Mohammad, Ahmad; Whitley, Kennedy C.; Fajardo, Val A.; MacPherson, Rebecca E. K.
Abstract : Duchenne muscular dystrophy (DMD) is a progressive muscle wasting disorder caused by a mutation in the dystrophin gene. In addition to muscle pathology, some patients with DMD will exhibit cognitive impairments with severity being linked to age and type of genetic mutation. Likewise, some studies have shown that mdx mice display impairments in spatial memory compared with wild‐type (WT) controls, while others have not observed any such effect. Most studies have utilized the traditional C57BL/10 (C57) mdx mouse, which exhibits a mild disease phenotype. Recently, the DBA/2J (D2) mdx mouse has emerged as a more severe and perhaps clinically relevant DMD model; however, studies examining cognitive function in these mice are limited. Thus, in this study we examined cognitive function in age‐matched C57 and D2 mdx mice along with their respective WT controls. Our findings show that 8‐ to 12‐week‐old C57 mdx mice did not display any differences in exploration time when challenged with a novel object recognition test. Conversely, age‐matched D2 mdx mice spent less time exploring objects in total as a well as less time exploring the novel object, suggestive of impaired recognition memory. Biochemical analyses of the D2 mdx brain revealed higher soluble amyloid precursor protein β (APPβ) and APP in the prefrontal cortex of mdx mice compared with WT, and lower soluble APPα in the hippocampus, suggestive of a shift towards amyloidogenesis and a similar pathogenesis to Alzheimer's disease. Furthermore, our study demonstrates the utility of the D2 mdx model in studying cognitive impairment. Abstract : Age‐matched D2 mdx mice spend less time exploring the novel object compared with wild‐type (WT), suggestive of impaired recognition memory. Biochemical analyses of the D2 mdx brain revealed higher soluble amyloid precursor protein β (APPβ) and APP in the prefrontal cortex of mdx mice compared with WT, and lower soluble APPα in the hippocampus, suggestive of a shift towards amyloidogenesis.